Mecanismos de encapsulación nominal en la prensa informativa: estudio contrastivo polaco-español - Bień, Janusz (Studia Romanica Posnaniensia, 2019)
Nominal encapsulators, also referred to by other terms coined in the Spanish tradition (discursive labels), are textual cohesion devices, frequently used in journalistic discourse to condense and summarize the predicative contents of a sentence or a textual sequence. These nominal units (nouns or syntagms) can synthesize texts of different length or even refer to discontinuous fragments. Apart from performing this very basic function founded on the discursive economy of the journalistic genre, the nominal encapsulators allow the author to recategorize the content of the encapsulated segment through different evaluative modifiers and therefore to obtain either a negative or a positive perception of the message by the reader. Given an apparent lack of research on the subject on encapsulation devoted to more than one language, our purpose is to carry out a contrastive analysis of the said phenomenon in Spanish and Polish in order to juxtapose the values and the frequency of usage of encapsulators with certain characteristics of both languages. Some formal as well as pragmatic and semantic features of nominal devices are thus analysed, namely their encapsulating mechanism, their degree of modification and some of their discursive functions.